Cashews for cash - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
In five years' time Ghana's Upper West Regional Administration will have planted 100,000 cashew and other economically profitable trees in a project financed by the United Nations Development Programme. The District assemblies in the five Districts...